1
$\begingroup$

There is the system:

$$ \left\{ \begin{array}{c} \dot{x} = -xy^2+x+y \\ \dot{y} = -x-y+x^2y \end{array} \right. $$

the way it should be solved is to find an integrable combination there is the description (page 349 of pdf document).

I've already tried multiplying the first equation by $x$, the second one by $y$ then adding first to second so I got: $xdx+ydy = x^2 - y^2$, which I have no idea how to integrate.

Also I tried multiplying the first by $y$, the second by $x$, also adding first to second so I got: $ydx+xdy=(xy - 1)(x^2 - y^2)$, which I also don't know how to integrate.

Could you plese provide any integrating combinations or ideas how to deal with equations I got.

$\endgroup$
1
$\begingroup$

That's a good start, except that you should write $\dot x$ and $\dot y$ instead of $dx$ and $dy$.

Anyway, you have $$ (\tfrac12 (x^2+y^2))\dot{} = x \dot x + y \dot y = x^2-y^2 $$ and $$ (xy)\dot{} = \dot x y + x \dot y = (xy-1)(x^2-y^2) . $$ These can be combined to give $$ (xy)\dot{} = (xy-1) (\tfrac12 (x^2+y^2))\dot{} $$ so that either $xy-1=0$ identically or $$ \frac{(xy)\dot{}}{xy-1} = (\tfrac12 (x^2+y^2))\dot{} $$ where both sides can be integrated to find a constant of motion.

Can you take it from there, or do you need further hints?

$\endgroup$
  • $\begingroup$ Thank you for the answer. I used your steps and got $ce^{x^2+y^2}=(xy-1)^2$. As I know after that we should express $x$ or $y$ from there and substitute the result to one of the equations so we get $x(t)$ or $y(t)$. Am I right or there is some another way get the answer (cause mine seems to be too complicated :)) $\endgroup$ – Егор Пономарёв Jun 6 at 20:57
  • $\begingroup$ There also was Cauchy problem in the task so I've tried to use to simplify my task. It is: $x(2)=1$, $y(2)=1$. I substituted it to the result above and got that $c=0$ hence $1=xy$ hence $x=\frac{1}{y}$. Then I substituted this to the second equation and got $\frac{dy}{y} = -dt$. Am I right doing this? $\endgroup$ – Егор Пономарёв Jun 6 at 21:25
  • 1
    $\begingroup$ @ЕгорПономарёв: Looks fine! I doubt it's possible to find expressions for $x(t)$ and $y(t)$ in the general case (in practice, that is; it's always possible in principle once you have a constant of motion). $\endgroup$ – Hans Lundmark Jun 7 at 5:02
  • $\begingroup$ Also, $\dot{x} + \dot{y} \equiv 0$, hence $\frac{d}{dt}(x(t) + y(t)) \equiv 0$ and $x(t) + y(t) \equiv x(0) + y(0)$. $\endgroup$ – Evgeny Jun 7 at 20:01
  • $\begingroup$ @Evgeny: No, that would have been too easy! Note that it's $\dot x + \dot y = -xy^2 + x^2 y = xy (x-y) \neq 0$. $\endgroup$ – Hans Lundmark Jun 7 at 20:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.